(3eNJda GdTjYI aj CMcGe GdTQjYIs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3efUhQ Hf Ydj Hf efUhQs)
(3ChdgG (B:s
(3GdebUO GdKGdK aj CaYGd GdML, hajg aUhd GdChd aj GdEMQGe(B...s
(3BNQgG (B:s
(3EbQGQ GdYbdGA Ydi CfaSge LGFR, hgPG YGbd CbQ HeMJed ajg cZjQg ef GdYbdGA hcd EbQGQ aEfg HNdGa GdXGgQ(B. (3Je GdLRA GdKGdK(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B284s
(3GdCYdGe(B: (3L(B2(3, (B227s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis